The Ramsey numbers of fans versus a complete graph of order five - Yanbo Zhang; Yaojun Chen (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2014)
For two given graphs F and H, the Ramsey number R(F,H) is the smallest integer N such that for any graph G of order N, either G contains F or the complement of G contains H. Let F_l denote a fan of order 2l+1, which is l triangles sharing exactly one vertex, and K_n a complete graph of order n. Surahmat et al. conjectured that R(F_l,K_n)=2l(n-1)+1 for l≥ n≥ 5. In this paper, we show that the conjecture is true for n=5.